Dust Exposure Monitoring: Abrasive Blasting Dust from Cleaning Process in Marine Industry - Zakaria, Hanis; Mohd Katman, Mohamad Khairul Hafiz; Mat, Muhammad Nur Hidayat; Sies, Mohamad Farid; Asmuin, Norzelawati (International Journal of Integrated Engineering, 2019)
Abrasive blasting is one of application that widely use in marine industry. This process is expected would release dust that believe can be harmful to human health such as cause of chronic obstructive pulmonary disease (COPD). In Malaysia, Ministry of Health report that the deadliness of COPD for men in Malaysia peaks at age 80 and above. COPD start kills men at the lowest rate at age 10-14.  This study to determine the dust released from abrasive blasting in cleaning process and effect to human worker. This experiment was conducted using establish method which is NIOSH 0500 and NIOSH 0600 for exposure monitoring process. Sample from exposure monitoring process were analysis using XRD for determine the composition of dust release from abrasive blasting activity. Result from study show that level of exposure to dust release from abrasive blasting activity are exceed from the limit under Occupational Safety and Health (USECHH) Regulations 2000. Silica dioxide and other hazardous composition found under XRD testing